Męskie fantazje – od freikorpsów do wszechpolaków [rec. Klaus Theweleit: Męskie fantazje. T. 1: Kobiety, strumienie, ciała, historia. T. 2: Męskie ciała. Przyczynek do psychoanalizy białego terroru. Przeł. Mateusz Falkowski, Michał Herer. Przekład przejrz - Śmieja, Wojciech (Śląskie Studia Polonistyczne, 2016)
The classic study of the German social anthropologist is discussed in the context of different trends in “masculinity studies”. The reviewer demonstrates that “male fantasies,” analysed by Theweleit, are not solely a historical phenomenon, but nowadays – in a slightly modified form – can urge young men to (often dangerous) actions. Moreover, Theweleit’s book is also worth reading because throughout almost the whole previous century the Polish variant of masculinity has been referring to the hegemonic German masculinity as its antithesis.